Is Curcumin at the Threshold of Therapeutic Effectiveness on Patients with Colon Cancer?—A Systematic Review - Shafei, Laila Khaled Ismael Abdelgawad; Mohamed Ibrahim, Mohamed Izham; Billa, Nashiru (Frontiers in Pharmacology, 2021)
Curcumin, obtained from curcuma longa, has been the subject of decades of scientific investigation on its therapeutic usefulness. It is reported to possess several therapeutic properties, of which anti-colon cancer is of interest in this review. Clinically however, curcumin has yet to firm up its place among established anti-colon cancer therapeutic contenders. We aimed to systematically review prevailing clinical evidence on the role of curcumin in colon cancer treatment. The review drawing from literature on clinical studies indicates fairly long term tolerability. No regression of tumor was reported when curcumin was the sole intervention. Increase in p53 level expression was reported in a placebo controlled study but no reduction in PGE2 or 5HETE. Pharmacokinetic data on healthy humans indicate that formulated curcumin delivery systems present significantly higher systemic bioavailability. It appears therefore that the clinical use of curcumin can potentially be realized only through appropriate formulation interventions.